The Effect of Using Metacognitive Skills in Teaching Mathematics on the Immediate and Delayed Achievement of Third Grade Students - Abu Khadra, Razan Jihad; Hamzeh , Mohammad AbdelWahab (Dirasat: Educational Sciences, 2023)
Objectives: The current study aimed to investigate the effect of using metacognitive skills in teaching mathematics on the immediate and delayed achievement of third grade students. Methods: An experimental method with quasi- experimental design was used. The sample of the study consisted of (153) male and female students from an intentionally chosen elementary school in the city of Amman. The sample was assigned randomly into two groups: an experimental group (77 male and female students), taught using metacognitive skills, and control group (76 male and female students), taught using the regular method. An achievement test that consisted of (30) items was developed after verifying its validity and reliability. Results: The results of the study showed that there were statistically significant differences at (α=0.05) in the students’ immediate achievement in favor of the experimental group, and that using metacognitive was effective in the delayed achievement. Conclusions: The study recommended the use of metacognitive skills in teaching the basic stage and the need to prepare a training program before and during the service to train on how to use and apply metacognitive skills in teaching mathematics to develop academic achievement.